2022
DOI: 10.3389/fbioe.2022.957435
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effects of medial meniscus radial tears on the knee joint during gait: A concurrent finite element musculoskeletal framework investigation

Abstract: The biomechanical variation in the knee during walking that accompanies medial meniscal radial tears stemming from knee osteoarthritis (OA) has not been explored. This study introduced a finite element musculoskeletal model using concurrent lower limb musculoskeletal dynamics and knee joint finite element analysis in a single framework and expanded the models to include knees with medial meniscal radial tears and total medial meniscectomy. The radial tears involved three locations: anterior horn, midbody, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…However, the tears were simulated as a tissue loss, which was located next to the posterior root. In the region of our simulated radial tear, the in‐silico model of Wang et al, however, indicated shear stresses instead of compression in their circumferential tensor plot, thus, being in agreement with our findings 55 . While the inside‐out suture repair was able to successfully restore the outer and middle tear sections, the more critical inner, avascularised region 53 of the tear was not repaired and still tended to gap (Figure 10).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the tears were simulated as a tissue loss, which was located next to the posterior root. In the region of our simulated radial tear, the in‐silico model of Wang et al, however, indicated shear stresses instead of compression in their circumferential tensor plot, thus, being in agreement with our findings 55 . While the inside‐out suture repair was able to successfully restore the outer and middle tear sections, the more critical inner, avascularised region 53 of the tear was not repaired and still tended to gap (Figure 10).…”
Section: Discussionsupporting
confidence: 90%
“…This appears to be a reasonable biomechanical behaviour, because the axial load, which is transferred via the convex-shaped surface of the medial femoral condyle, results in a splitting force which is normal to the meniscus surface. 54 A reverse behaviour was observed in the only study to quantify radial tears in in-silico by Wang et al 55 In their finite element model, radial tears were investigated at the medial posterior horn and compression forces were detected at the tear ends, causing the fragments to converge.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…12,123 Wang et al found that a radially wider incomplete tear of the medial meniscus could disrupt the circumferential stress transmission in the meniscus and that higher stresses at the end put the meniscus at risk of complete rupture. 124 It has been suggested that the maximum contact stress on the articular cartilage after meniscectomy was approximately twice that of a healthy joint, 125 with a significant increase in stress-strain on the lateral cartilage, 126 which might help to explain the cartilage damage and degeneration observed after meniscectomy. Meniscus replacement might delay long-term adverse events such as OA.…”
Section: Meniscus Injurymentioning
confidence: 99%
“…We set bone as a rigid material [18] and articular cartilage as an isotropic linear elastic material [19]. The materials of the anterior and posterior cruciate ligaments are set as Neo-Hookean hyperelastic materials, and other ligament materials are set as isotropic linear elastic materials [17,19]. The meniscus provided resistance against shear forces within the joint cavity and prevented outward expansion.…”
Section: Materials and Propertiesmentioning
confidence: 99%